2014
DOI: 10.5815/ijcnis.2015.01.05
|View full text |Cite
|
Sign up to set email alerts
|

An Improvement over a Server-less‎ RFID Authentication Protocol

Abstract: With the increased radio frequency identification (RFID) applications different authentication schemes have been proposed in order to meet the required properties. In this paper we analyze the security of a server-less RFID authentication protocol which is proposed by Deng et al. in 2014. Deng et al. proposed an improvement over Hoque et al. protocol to overcome its vulnerability against data desynchronization attack. However, in this paper we show that their protocol is still vulnerable against data desynchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Deng et al also improved Hoque et al's [29] authentication protocol in order to withstand data desynchronization attacks. However, the authors of [31] found that Deng et al's protocol is still vulnerable to data desynchronization attack after two protocol runs. In 2015, Abdolmaleky et al [32] proposed a protocol to address the weaknesses found in the protocols proposed by Hoque et al [29] and Deng et al [30], which are tag impersonation and reader impersonation attacks.…”
Section: Rfid Authentication Protocolsmentioning
confidence: 99%
“…Deng et al also improved Hoque et al's [29] authentication protocol in order to withstand data desynchronization attacks. However, the authors of [31] found that Deng et al's protocol is still vulnerable to data desynchronization attack after two protocol runs. In 2015, Abdolmaleky et al [32] proposed a protocol to address the weaknesses found in the protocols proposed by Hoque et al [29] and Deng et al [30], which are tag impersonation and reader impersonation attacks.…”
Section: Rfid Authentication Protocolsmentioning
confidence: 99%
“…'s [15] authentication protocol in order to withstand data desynchronisation attacks. However, the authors of [17] found that Deng et al . 's protocol is still vulnerable to data desynchronisation attack after two protocol runs.…”
Section: Related Workmentioning
confidence: 99%